Boosting the electrochemical activities of MnO2 for next-generation supercapacitor application: Adaptation of multiple approaches. (1st July 2023) - Khalid, Muhammad Usman; Katubi, Khadijah Mohammedsaleh; Zulfiqar, Sonia; Alrowaili, Z.A.; Aadil, Muhammad; Al-Buriahi, M.S.; Shahid, Muhammad; Warsi, Muhammad Farooq
Graphical abstract: Highlights: Hydrothermal synthesis of Ag-MnO2 NWs and their MXene reinforced composite. The effects of nanotechnology, doping, and making composites on the way electrode materials behave electrochemically are explained. Multiple techniques are used to achieve significant increases in specific conductivity and surface area. The electrochemical properties of the Ag-MnO2 /MXene@NF electrode are superior to those of the MnO2 @NF and Ag-MnO2 @NF electrodes. The Ag-MnO2/MXene@NF electrode had a high specific capacitance of 1188 F g −1 at 1 A g −1 and a capacitance retention of 96.4 % after 6000 cycles. Abstract: A novel Ag-MnO2 /MXene on nickel foam (Ag-MnO2 /MXene@NF) electrode has been developed by incorporating hydrothermal and post-sonication processes. Ag-doping, MXene reinforcement, nanotechnology approaches, and highly porous current collector (Nickel foam) play a decisive role in boosting the overall activity of the Ag-MnO2 /MXene@NF. The Ag-doping tunes the band structure of MnO2 and intrinsically improves its specific conductivity. At the same time, the sandwiching of Ag-MnO2 NWs between the MXene sheet's voids and their dispersion over the MXene sheet's surface led to the formation of a hetero-structured composite with superb conductivity, a high surface area, lower crystallinity, and structural openings. The nanostructured nature of MnO2 (NWs) and their addition to MXene, a conductive and porous matrix, resulted in better capacitance retention and faster ion diffusion. The nano-sized and spongy structure of the Ag-MnO2 /MXene@NF not only exposes the bulk of the electrode for charge storage but also buffers the electrode from pulverization as a result of tedious cyclic tests and facilitates the electrolyte ions' mobility. These induced features enabled the Ag-MnO2 /MXene@NF to show a higher capacitance of 1188 F g −1 @ 1Ag −1, impressive rate capability (85.8 % @9 A g −1 ), and superb cyclic activity of 96.4 % after 6000 tests. The combination of various techniques boosts the overall electrochemical performance of our developed Ag-MnO2 /MXene electrode, making it an acceptable option for use in advanced energy storage devices.